Effect of blended learning environment model on high school students' academic achievement - Kazu, Ibrahim Yasar; Demirkol, Mehmet (My University, 2014)
This study analyzes the students' academic performance by comparing the blended learning environment and traditional learning environment. It has been observed whether there is a significant difference between the academic achievement grade dispersions and the male-female students' grades. The study has been carried out in Diyarbakir Anatolian High School in 2010-2011 academic year first semester biology courses. For the study, two quantitive courses sections have been selected among the classes formed by secondary school senior students. Cluster analysis has been conducted to provide the objectivity when forming the experiment and control groups. The study has been conducted with 54 participants, 19 males and 8 females for the experiment group and 18 males and 9 females for the control group. The experiment group continued its education in blended learning environment and the control group continued its education in traditional learning environment. The created learning environments have focused the genetics topic of the biology course and lasted for 6 weeks. During the study, pre-test and final-test have been used for the academic achievement analysis. According to the results acquired at the end of the study, a significant difference hasn't been found between the two groups at the end of the pre-test applied to experiment and control groups. Besides, in accordance with the averages of the final test grades, the experiment group has been found more successful than the control group. In both of the learning environments, female students have turned out to be more successful than the male students. © The Turkish Online Journal of Educational Technology.
Keywords: Academic achievement; Blended learning; Face to face learning; Online learning